PERSEPSI DAN KESIAPAN GURU MATA PELAJARAN SAINS SMP MUHAMMADIYAH SE-KOTA SURABAYA TENTANG PELAKSANAAN KURIKULUM 2013 - Putri Rizky Rachmawati; Yuni Gayatri; Ruspeni Daesusi (Universitas Muhammadiyah Surabaya, 2017)
This study aimed to determine the readiness of teachers' perceptions and science subjects in SMP Muhammadiyah of Surabaya on the implementation of Curriculum 2013 and discoverd the obstacles facing teachers. The subjects were teachers of science subjects in SMP Muhammadiyah of Surabaya, by sampling quotas with interview and descriptive analysis. The final conclusion (1). Teachers of Science Subjects in SMP Muhammadiyah of Surabaya found Curriculum 2013 that had been a good year because it could make students active and able to learn the problems faced. The 2013 Curriculum for science subjects was in conformity applied to the junior high school students, as a solution to the shortcomings inherent in the SBC, and the form of the government's efforts to advance the next generation; (2). Generally Teachers of Science Subjects in SMP Muhammadiyah of Surabaya that had conducted the Readiness of 2013 Curriculum. It appeared from the preparation of lesson plan that was in accordance with the technical guidelines lesson plan in the 2013 Curriculum. The training curriculum of 2013 had been followed; (3). The obstacles encountered mostly teachers on curriculum assessment system in 2013, considered by many, complex, and required a longer time to completion.Keywords: Perception, Readiness of Teachers, 2013 Curriculum